Understanding autism spectrum disorder and social functioning in children with neurofibromatosis type 1: protocol for a cross-sectional multimodal study. Issue 9 (26th September 2019) - Haebich, Kristina M; Pride, Natalie A; Walsh, Karin S; Chisholm, Anita; Rouel, Melissa; Maier, Alice; Anderson, Vicki; Barton, Belinda; Silk, Tim; Korgaonkar, Mayuresh; Seal, Marc; Lami, Francesca; et al.
Abstract : Introduction: Children with the single-gene disorder neurofibromatosis type 1 (NF1) appear to be at an increased risk for autism spectrum disorder (ASD) and exhibit a unique social-cognitive phenotype compared with children with idiopathic ASD. A complete framework is required to better understand autism in NF1, from neurobiological levels through to behavioural and functional outcomes. The primary aims of this study are to establish the frequency of ASD in children with NF1, examine the social cognitive phenotype, investigate the neuropsychological processes contributing to ASD symptoms and poor social functioning in children with NF1, and to investigate novel structural and functional neurobiological markers of ASD and social dysfunction in NF1. The secondary aim of this study is to compare the neuropsychological and neurobiological features of ASD in children with NF1 to a matched group of patients with idiopathic ASD. Methods and analysis: This is an international, multisite, prospective, cross-sectional cohort study of children with NF1, idiopathic ASD and typically developing (TD) controls. Participants will be 200 children with NF1 (3–15 years of age), 70 TD participants (3–15 years) and 35 children with idiopathic ASD (7–15 years). Idiopathic ASD and NF1 cases will be matched on age, sex and intelligence. All participants will complete cognitive testing and parents will rate their child's behaviour on standardised questionnaires. Neuroimaging will be completed by a subset of participants aged 7 years and older. Children with NF1 that screen at risk for ASD on the parent-rated Social Responsiveness Scale 2nd Edition will be invited back to complete the Autism Diagnostic Observation Scale 2nd Edition and Autism Diagnostic Interview-Revised to determine whether they fulfil ASD diagnostic criteria. Ethics and dissemination: This study has hospital ethics approval and the results will be disseminated through peer-reviewed publications and international conferences.